KONSEP MUHAMMAD SHAHRU TENTANG AURAT PEREMPUAN - Laila Nurul hidayah (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2020)
In Islam, clothing does not only function as jewelry and body armor from heat and cold, but more importantly is to cover the nakedness. Al-Qur'an al-Karim shows the obligation of women to cover their bodies in His words, "And let them not show their jewels, except those which (normally) appear from them,". Parts of female limbs that are not allowed to be seen by others are aurat. Islamic scholars agree that all women's bodies are aurat, in addition to the face and two palms. What is meant by the jewelry that appears is the face and two palms. While what is meant by khimar is a headgear, not a face covering like a veil, and what is meant by jaib is chest. The women have been ordered to put a cloth over his head and spread it to cover her chest. By doing library research, that is, research whose main object is books or other sources of literature, meaning that data is sought and found through literature review of books relevant to the discussion, a minimum limit of aurat according to Muhammad Shahrur is that dress cover the juyub, while the maximum limit is dressing which covers all parts of the body besides the face and palms.